Sustainable Agricultural Development in Nigeria: A Way Out of Hunger and Poverty - Nwankpa, Nneka (European Journal of Sustainable Development, 2017)
This paper examines the agricultural transformation via-a-vis hunger and poverty eradication as a means of sustaining economic growth and development in Nigeria. About 80 percent of Nigerians live in rural areas and agricultural sector remains the main provider of livelihood for most rural dwellers and a major contributor to Nigeria growth rate besides oil and gas sector. Before the discovery of crude oil in commercial quantity in the country in 1968, agriculture dominated the economy and accounted for almost all its foreign reserves. The discovery of oil caused a paradigm shift from agriculture to petroleum, relegating the multi-functional nature of agriculture to the background. Despite the huge revenue and foreign reserves derived from the oil sector, hunger and poverty rates remain on the increase in Nigeria. Recent estimates put the number of undernourished Nigerians at over 53 million-representing about 30 percent of the country’s total population while the poverty statistics shows that about 72 percent of Nigerians (118.2million people) are poor. The importance of agricultural transformation on the nation’s socio-economic development cannot be over-emphasized. Hunger and poverty rates will continue to rise as long as the abundance human and material resources located in Nigeria rural settings are not optimally harnessed. This paper therefore, emphasizes significant improvements and effective harnessing of agricultural sector for meaningful and adequate food production and other socio-economic developments through agricultural reforms. Specifically, the study limits itself to the important role of agricultural transformation in engendering sustainable development and significant levels of hunger and poverty reduction in South Western Nigeria. Keywords: Hunger, Agricultural transformation, Food production, Poverty reduction, Sustenance